2021
DOI: 10.1136/bmjopen-2020-037154
|View full text |Cite
|
Sign up to set email alerts
|

Rates and risk factors for suicidal ideation, suicide attempts and suicide deaths in persons with HIV: a protocol for a systematic review and meta-analysis

Abstract: IntroductionThe prevalence of HIV/AIDS is high and is associated with psychiatric morbidity and suicide risk. The objective of this study will be to assess the rates of suicidal ideation, suicide attempts and suicide deaths in people living with HIV/AIDS (PLWHA).Methods and analysisWe present a study protocol for a systematic review and meta-analysis of studies reporting the suicidality outcomes (suicidal ideation, suicide attempts and suicide deaths) in PLWHA. PubMed (MEDLINE), Scopus, EMBASE, Cochrane Librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This study has been registered with PROSPERO (registration number: CRD42020161501) and the protocol is published. 18 This study is being reported per the reporting guidance provided in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement (see online supplemental table 1). 17 We used the study protocol (online supplemental text 1).…”
Section: Database Searches Search Strategy and Termsmentioning
confidence: 99%
“…This study has been registered with PROSPERO (registration number: CRD42020161501) and the protocol is published. 18 This study is being reported per the reporting guidance provided in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement (see online supplemental table 1). 17 We used the study protocol (online supplemental text 1).…”
Section: Database Searches Search Strategy and Termsmentioning
confidence: 99%
“…However, there was no significant age difference among people with chronic HIV infection. On the contrary, among the studied subjects with HIV-negative status, the level of anxiety increases with increasing age [15,31].…”
Section: Mental Disorders Structure Smith Colin M Kennedy Et Al "Amer...mentioning
confidence: 76%
“…Studies focused on inflammatory pathology seem to describe an increased risk of suicide in people with SLE [ 45 ], a finding that we have not been able to corroborate given the lack presence of people with SLE in our sample. In the case of HIV infection, studies have linked it to suicide in the presence of other psychiatric comorbidities [ 46 ].…”
Section: Discussionmentioning
confidence: 99%